Challenges of Drinking Water Supply in Indonesian Cities: A Brief Review - Ihsan, Taufiq; Ilfan, Freddy (LPPM Universitas Andalas, 2025)
The supply of safe drinking water in the developing world, particularly in Indonesia, has remained one of the major challenges. Millions are still without access to clean water, which inflicts public health and has negative implications for socioeconomic development. This paper elaborates on the multifaceted challenges facing the drinking water supply in Indonesian cities, from inconsistent policies and lack of autonomy for Water Agencies to aging infrastructure, unreliable power supply, and inadequate investment. Brief case studies from Jakarta, Surabaya, and Padang plainly bring out the specificity of issues in various cities. The paper suggests that solutions can lie in policy reform, empowering the water agencies, fighting corruption, greater investment in infrastructure, making the most of pricing and cost recovery, and strategic engagement with the private sector. Unless these are addressed, such challenges will persist in hindering the progress of Indonesia toward the universal access goal for all urban residents to sufficient, safe, reliable, and affordable drinking water